Memes as symbols of hate speech: The influence of graphic humour on freedom of expression and politics - Aranda Serna, Francisco José (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
Internet memes have become a cultural and artistic expression of the most popular social networks. Memes are graphic expressions accompanied by a small text that reflect and idea or current news with a certain humorous tone that become viral very easily. This article aims to address the problem of the spread of hate speech through memes that take place on social networks. This dissemination of hate speech through memes is especially relevant in politics and some significant examples of political memes will be analysed to highlight their great influence in the celebration of elections.